Dopamine Contents in Hom Thong Bananas during Storage at 14 and 25oC - จันทราอภิรักษ์ ศุภิสรา; ร่มโพธิ์ภักดิ์ ธีรนุต; แก้วประสิทธิ์ จงรักษ์; ลอยสรวงสิน อาทร (YRU Journal of Science and Technology, 2018)
This research was focus on determination of dopamine contents containing in the pulp of Hom Thong bananas kept as a whole bunch for various times of storage at 14 และ 25 OC using a high performance liquid chromatography (HPLC). It was found that storage at 14 OC could retard the ripening of bananas at the 2nd ripeness stage (skin color: light green) as long as 21 days on which the maximum amount of dopamine was determined as high as 378.99/kg FW. The bananas were stored at 14 OC for 45 and 51 days, not matured at 4-6 (skin color: more yellow than green – all yellow). Whereas bananas kept at 25 OC could reach the 2nd ripeness stage within 4 days and had a dosage of 48.04 mg/kg FW, which was lower than that found in ripe bananas at 4th-6th stages (65.45-87.99 mg/1 kg FW)